Assessing Job Stress Factors among Medical Emergency Technicians 115 of Kerman - L Vali; M ,Amini Zade; T Sharifi; N Oroomiei; S Mirzaee; R Ghorbani nia (Tehran University of Medical Sciences, 2014)
Abstract Background: EMS technicians are faced with numerous stressful situations during a working day. These mental tensions may significantly effect on delivered services quality actually. This situation can be considered as a threaten risk for people who use the EMS. This study aimed to determine the most common stressful factors influencing the EMS technicians in Kerman. Materials Methods: In this cross-sectional study 140 EMS technicians participated. Sampling method was census and data collection was done by using a valid and reliable nursing tension factors questionnaire. Data analyzing was performed by SPSS software version 19 using Pearson correlation coefficient, Spearman and regression tests. Results: The most and least common stressful factors were patient care (Mean=3.24) and environmental tension (Mean=2.64) respectively. Regression analysis revealed significant relation between age and environment tension factors (β = -0.155, p=0.034,) and managerial stressful factors had significant relation with gender (β= -2.955, p= 0.047) and educational level of EMS technicians (β= -0.23,p=0.05). Conclusion: Patient care and personal factors cause stressful situations among EMS technicians. Therefore, it is recommended emergency managers to provide strategies toward decreasing job stress in order to improve the quality of working life and organizational commitment to help EMS technicians.